Comparative Evaluation of Three Chitin Synthesis Inhibitor Termite Baits Using Multiple Bioassay Designs - Bal Krishna Gautam; Gregg Henderson (Sociobiology)
Use of chitin synthesis inhibitors has revolutionized the potential impact of termite baiting systems. Several chitin synthesis inhibitors have been used or tested against subterranean termites. We evaluated the effect of lufenuron on bait matrix consumption and mortality of Coptotermes formosanus and compared it with 2 other chitin synthesis inhibitors presently used for termite control: diflubenzuron and noviflumuron. Laboratory no-choice and multi-chamber bioassay designs were employed. At the end of 6 weeks, in both the no-choice and multi-chamber tests, mortality was significantly higher in all the chitin synthesis inhibitor treatments as compared to the controls; however, lufenuron treatment had significantly higher mortality than the other chitin synthesis inhibitors. Multi-chamber tests suggested no sign of feeding deterrence with any of the chitin synthesis inhibitors at the concentrations tested. Consumption of lufenuron cardboard or noviflumuron bait matrix was similar to that of control cardboard in the no-choice tests. We conclude that, based on the overall bait consumption and mortality data, lufenuron was at least as effective as noviflumuron and diflubenzuron.